PRIVATE INFORMATION ARRIVAL AT INDONESIA STOCK EXCHANGE, REALITY OR IMAGINARY? U-SHAPED RETURN VARIANCE CURVE VERIFICATION - Mihardjo, Setiyono; Sumiyana, Sumiyana (Journal of Indonesian Economy and Business, 2012)
This research investigates occurrence of private information arrival in Indonesia Stock Exchange (IDX). The occurrence comes from overnight nontrading session as well as lunch-break hour. Lunch-break return variance decreases two times in comparison with early morning and lately afternoon return variances. This variance is due to private information arrival. This study finds that opening prices form the full day U-shape. It means that opening price causes stock mispricing. It also be concluded that lunch-break session produces the bottom line on the U-shape to move downward. U-shaped curve during morning until the end-afternoon session occurs. Therefore, the line formationimplies the existence of private information arrival that is in short-lived.Keywords: U-shaped curve, private and public information